STRUCTURAL-CONTENTAL DEFINITENESS OF ACTUALIZATION OF ATHLETES' THINKING TYPES IN THE CONTEXT OF THE SYSTEM-ACTIVITY APPROACH - Kim, T.K.; Pleshakov, A.A.; Kuzmenko, G.A.; Ivankov, Ch.T. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the conjugation of the types of thinking in the context of the structural-content components of the athlete's activity in the implementation of intellectual tasks in the process of learning motor actions. Methods and structure of the study. In the course of scientific work, questioning and interviewing of coaches were carried out on the issues of updating the types of thinking in adolescent athletes in the structural components of activity. 34 sports coaches took part in the study. Results and conclusions. Analysis of the results showed that the largest factorial weights in improving the technique of a sport are characterized by: to understand the significance of the process of improvement - strategic (0.897); for the implementation and adjustment of the program of behavior - situational / practical (0.843), prognostic (0.877), spatial (0.724), figurative (0.766), critical thinking (0.747). At the same time, it is noted that taking into account the peculiarities of the manifestation of the types of thinking in young athletes in the implementation of the intellectual tasks of sports activities will allow to identify the most problematic areas of the coordinated anticipatory involvement of the types of thinking in segments of the structural components of the activity and optimize the process of learning the technique of motor actions, as well as improve individual technical and tactical skills. athlete.